The effect of community involvement and perceived impact on residents' overall well-being: Evidence in Malang marine tourism - Riyanto; Mohammad Iqbal; Supriono; Muhamad Robith Alil Fahmi; Eliana Sandy Yuliaji (Cogent Business & Management, 2023)
This study investigates and examines the relationship between community involvement in the tourism development community and its perceived environmental, sociocultural, and economic impacts on the welfare of local tourism residents. A quantitative approach is used in this study. This involved the design of a questionnaire as a research instrument, and its distribution to 175 respondents who are local residents of the coast of Malang Regency. PLS-SEM was used to analyze the data. The results of the study indicate that all direct relationships contribute a negative but not significant effect to the perceived economic impact on resident well-being. Furthermore, the mediating role of perceived tourism impact on the relationship between community involvement and resident well-being shows that perceived economic impact mediates negatively but not significantly. Conversely, perceived environmental and sociocultural impacts mediate positively and significantly. Tourism, as a basis for social and economic influence on local communities involved in the development of tourist destinations, certainly needs to be considered. The measurement of local people's perceptions of welfare in the tourism sector can empirically capture existing conditions.
Keywords: 650; community involvement; perceived tourism impact; resident well-being; social exchange theory